Effect of the Noninvasive Follicular Thyroid Neoplasm With Papillary-Like Nuclear Features (NIFTP) Nomenclature Revision on Indian Thyroid Fine-Needle Aspiration Practice. Issue 2 (20th February 2021) - Rana, Chanchal; Ramakant, Pooja; Goel, Divya; Singh, Akanksha; Singh, KulRanjan; Babu, Suresh; Mishra, Anand
Abstract: Objectives: To analyze risk of malignancy (ROM) in Bethesda categories (BCs) and the impact of noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP) reclassification on malignancy risk and surgical outcome. Methods: In this retrospective study based on fine-needle aspiration samples with histologic follow-up, ROM was analyzed in BCs. Possible cases of NIFTP were reviewed, followed by the analysis of impact of this reclassification on ROM in BCs. Results: The incidence of NIFTP was 6.9% among excised thyroid nodules and 16.8% among all resected neoplastic lesions. ROM for BCs I to VI was 37.5%, 9.6%, 40.0%, 46.5%, 88.8%, and 96.8%, respectively. Risk of neoplasia was 50.0%, 13.8%, 55.0%, 71.2%, 88.8%, and 96.8% respectively. When NIFTPs were considered nonmalignant lesions, ROM decreased by 6.3%, 4.3%, 20%, 19.1%, 22.5%, and 1.5% in each Bethesda category (I-VI), respectively. Inability to diagnose NIFTP preoperatively led to overtreatment in 16.2%. Conclusions: Prevalence of NIFTP in Asian countries may be higher than expected. Substantial cases of NIFTP have a benign preoperative cytology; hence, cases of follicular adenoma and adenomatous colloid nodule should be included in the review. NIFTP reclassification has significantly reduced the ROM in indeterminate BCs, suggesting diagnostic lobectomy rather than total thyroidectomy. Countries should establish their own malignancy risk range and parameters.